Magnetic ordering phase transition and abnormal brittleness in dilute Fe–Mn solid solution - Wei Liu; Yunfeng Liang; Xiangyan Li; Yichun Xu; Yange Zhang; Wenliang Li; Q.F. Fang; Caetano R. Miranda; Chuan-Lu Yang; C.S. Liu; Xuebang Wu (Journal of Materials Research and Technology)
Experiments showed an antiferromagnetic (AFM)-to-ferromagnetic (FM) phase transition in the Fe–Mn solid solution as the Mn content increases to about 2 at.%. Surprisingly, just approximately from this concentration to 4.8 at.% Mn, Mn-bearing steel becomes very brittle, completely denying its metallic nature. However, mechanisms for the magnetic ordering phase transition and the extraordinary brittleness remain unclear. Based on magnetism-constrained/unconstrained calculations and ab initio molecular dynamics simulations within density functional theory, we show that while the AFM phase prevails at low Mn contents, the FM phase becomes dominant at 1.85 at.% Mn under elevated temperatures and pressures. We show that the phase transition involves electron transfer among 3d states of Mn, revealing a clear difference in the mechanical properties. Furthermore, our results suggest that the AFM−FM phase transition with increasing Mn concentration is correlated to the thermal effect. With this in mind, a concentration and temperature phase diagram at the low-Mn content regime was constructed. It is noted that the abnormal brittleness might be related to the stress variations resulting from the local Fe–Mn magnetic coupling phase changes within the grains.